DIGITAL DISRUPTION: PELUANG ATAU ANCAMAN BAGI EKSISTENSI PROFESI AKUNTAN DI MASA DEPAN - Sofie Yunida Putri (BAJ: Behavioral Accounting Journal, 2019)
This study aims to examine the impact, both opportunities and threats, of digital disruption on the existence of the accounting profession in the future. This is a qualitative research with a transcendental phenomenology approach, which explores accountants' perspectives related to the digital disruption phenomenon faced by the accounting profession. Data collection was carried out with a semi-structured interview technique of three key informants who worked as educators at UPN "Veteran" Jawa Timur. The impact of digital disruption in this research is the impact of the use of virtual classroom systems on accountant educators and the use of accounting software for accountants. The results of this study indicate that digital disruption has no impact on the existence of the accounting profession as long as the accountant is able to adapt to technological developments. Therefore, to maintain its existence, an accountant must be able to adapt to technological developments and increase his mastery of knowledge.